Register role and function in the arena of sociocultural practice (critical study of sociocultural practice) - Sujarwa, Sujarwa; Purwasito, Andrik; Habsari, Sri Kusuma; Pitana, Titis Srimuda (Universitas Ahmad Dahlan, 2023)
This paper is entitled